2021
DOI: 10.1155/2021/2799415
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of Fabricated Synthetic Midthoracic Paediatric Spine as Compared to the Porcine Spine Based on Range of Motion (ROM)

Abstract: The present study is aimed at investigating the mechanical behaviour of fabricated synthetic midthoracic paediatric spine based on range of motion (ROM) as compared to porcine spine as the biological specimen. The main interest was to ensure that the fabricated synthetic model could mimic the biological specimen behaviour. The synthetic paediatric spine was designed as a 200% scaled-up model to fit into the Bionix Servohydraulic spine simulator. Biomechanical tests were conducted to measure the ROM and nonline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…As presented in Figure 5, the ROM from experimental data increased significantly (by 50%) from ±2 Nm to ±3 Nm loads, which suggested that the synthetic paediatric spine was more flexible after the ±2 Nm loads. Further analysis of the synthetic FE model was carried out to compare the ROM against the experimental data [17]. Based on the average percentage differences, the synthetic FE model ROM at ±2 Nm loads for the flexion/extension and lateral bending movements were the closest to the experimental result of paediatric ROM.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…As presented in Figure 5, the ROM from experimental data increased significantly (by 50%) from ±2 Nm to ±3 Nm loads, which suggested that the synthetic paediatric spine was more flexible after the ±2 Nm loads. Further analysis of the synthetic FE model was carried out to compare the ROM against the experimental data [17]. Based on the average percentage differences, the synthetic FE model ROM at ±2 Nm loads for the flexion/extension and lateral bending movements were the closest to the experimental result of paediatric ROM.…”
Section: Resultsmentioning
confidence: 97%
“…Further analysis of the synthetic FE model was carried out to compare the ROM against the experimental data [ 17 ]. Based on the average percentage differences, the synthetic FE model ROM at ±2 Nm loads for the flexion/extension and lateral bending movements were the closest to the experimental result of paediatric ROM.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations